PENGARUH KEADILAN PERPAJAKAN, SISTEM PERPAJAKAN, DISKRIMINASI, TEKNOLOGI DAN INFORMASI PERPAJAKAN TERHADAP PENGGELAPAN PAJAK (TAX EVASION) WAJIB PAJAK BADAN DI KANTOR PELAYANAN PAJAK PRATAMA DENPASAR TIMUR - Ni Kadek Seli Anggayasti; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2020)
Tax has an important component in a country to carry out national development. In each year the largest contribution in state revenue to meet the APBN posture in tax revenues is approximately 70%. Thus, taxes become one of the largest funds for routine expenditure and development expenditure in the receipt of government funds in the State. The Effect of Tax Justice, Taxation System, Discrimination, Technology and Tax Information on Tax Evasion becomes the objective to find out more about the influence of each variable. The number of samples used in this study were 100 corporate taxpayers. Data collection techniques using a questionnaire. This research uses multiple regression analysis method with technical data analysis using descriptive test, data instrument test, and classic assumption test. The results showed that Tax Justice has an influence on tax evasion (tvalue taxation) for the Tax Justice variable which is 2,366 and significant that is equal to 0.020 <0.05, Taxation system has an influence on tax evasion (tax evasion) t-value for the Taxation System variable is 2,287 and a significance of 0.024 <0.05, Tax Discrimination has an effect on tax evasion t-value for the Tax Discrimination variable which is 2,232 and significant is 0.035 <0.05, Technology and Information taxation has the influence of the tax evasion (tax evasion) value of the t-count for the variable Technology and tax information is 2,181 and significant that is equal to 0.036 <0.05.